Condutividade iônica e atividade termodinâmica em vidros x AgI (1-x) AgPO3, 0 ≤ x ≤ 0,5 - Bragatto, Caio Barca (Universidade Federal de São Carlos, 2012)
The ionic conductivity in solids is known since the 19th century, but the mechanisms of charge carriers transportation in amorphus solids is not yet fully known. The control of ths property is especially important for the development of fast ionic conductors (FICs) that can be applied in cell storage in electrochemical cells or in selective membranes. Through the dissolution of halogenate salts in a vitreous matrix, we can observe an increase of up to five orders of magnitude in the ionic conductivity of some glasses. To investigate this great variation of ionic conductivity, we propose a model based in the “weak electrolyte theory”. This theory, that says that the glass is a solution where the modifier (solute) is weakly dissociated in the vitreous matrix (solvent), was proposed in the 70’s to explain the non-linear increase of ionic conductivity in glasses with the increase of network modifiers (alkaline oxides). Were sintetized glasses from the family x AgI (1-x) AgPO3. The characterization showed interesting results, specially in the x ray diffraction, with the detection of a second amorfous halo for compositions with higher AgI content. Also, were realized impedance spectroscopy measurements, with a wide range of temperature, to determine the conductivity of the samples. To verify the proposed model, we proposed an experiment based in electrochemical cells, in wich we relate the electromotive force with chemical activity of AgI in the glass. We tested two methods to measure the activity of AgI: the first uses two batteries – one wich is a reference, using pure AgI, and the second with the glasses x AgI (1-x) AgPO3 . The second method is a concentration cell.
Keywords: Vidro; Termodinâmica; Condutividade iônica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA